2018
DOI: 10.3758/s13423-018-1459-0
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between theory of mind and executive functioning: A developmental cognitive neuroscience perspective

Abstract: Theory of mind (ToM) and executive functioning (EF) show marked interrelatedness across childhood, and developmental psychologists have long been interested in understanding the nature of this association. The present review addresses this issue from a cognitive neuroscience perspective by exploring three hypotheses regarding their functional overlap: (1) ToM relies on EF (EF→ToM); (2) EF relies on ToM (ToM→EF); and (3) ToM and EF are mutually related, owing to shared neural structures or networks (ToM↔EF). Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 225 publications
(230 reference statements)
10
95
0
8
Order By: Relevance
“…Wade et al (2018) summarized that the different ToM abilities are related to areas such as the bilateral temporoparietal junction (the inferior parietal lobule at the junction with the posterior temporal cortex), medial prefrontal cortex (including the anterior paracingulate cortex), precuneus/posterior cingulate cortex (including anterior paracingulate cortex), and sulcus temporalis superior/middle temporal gyrus. Wade et al (2018) summarized that the different ToM abilities are related to areas such as the bilateral temporoparietal junction (the inferior parietal lobule at the junction with the posterior temporal cortex), medial prefrontal cortex (including the anterior paracingulate cortex), precuneus/posterior cingulate cortex (including anterior paracingulate cortex), and sulcus temporalis superior/middle temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wade et al (2018) summarized that the different ToM abilities are related to areas such as the bilateral temporoparietal junction (the inferior parietal lobule at the junction with the posterior temporal cortex), medial prefrontal cortex (including the anterior paracingulate cortex), precuneus/posterior cingulate cortex (including anterior paracingulate cortex), and sulcus temporalis superior/middle temporal gyrus. Wade et al (2018) summarized that the different ToM abilities are related to areas such as the bilateral temporoparietal junction (the inferior parietal lobule at the junction with the posterior temporal cortex), medial prefrontal cortex (including the anterior paracingulate cortex), precuneus/posterior cingulate cortex (including anterior paracingulate cortex), and sulcus temporalis superior/middle temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and lesion studies in these patient groups have also helped to identify underlying neuronal networks ascribed to ToM and executive functions. Wade et al (2018) (Wade et al, 2018). The authors concluded that ToM skills and executive capabilities are based on partially overlapping networks comprising the medial prefrontal cortex, inferior parietal lobule, temporoparietal junction, and inferior frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of our explorative study is to fill the above-mentioned knowledge gap by assessing the contribution of RS functional connectivity (RS-FC) abnormalities to social cognition in patients with MS. Since some studies report an association between social cognition and cognitive abilities, both in healthy (Apperly et al, 2009;Wade et al, 2018) and in MS patients (Raimo et al, 2017), we explored RS networks mainly associated with high-level cognitive and/or social abilities: (1) the default mode network (DMN), which actively supports several aspects of cognition, like working memory, memory retrieval, or divergent thinking (Spreng, 2012;Murphy et al, 2018);…”
mentioning
confidence: 99%
“…For example, it should be noted that toddlerhood is characterized by the development of other aspects of cognitive development, such as executive functioning (Garon, Bryson, & Smith, ). Neuroimaging studies show that brain regions involved in theory of mind, such as the medial prefrontal cortex and temporo‐parietal junction, show substantial overlap with brain regions engaged in executive functioning (Rothmayr et al, ; Wade, Prime, et al, ). The simultaneous investigation of multiple aspects of early cognitive development in relation to children's brain development, parental beliefs, parenting behavior, and social development is an important challenge for future studies.…”
Section: Discussionmentioning
confidence: 99%